2017
DOI: 10.1103/physrevb.96.144412
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and current-induced motion of antiskyrmion in the presence of anisotropic Dzyaloshinskii-Moriya interaction

Abstract: Abstract:Topological defects in magnetism have attracted great attention due to fundamental research interests and potential novel spintronics applications. Rich examples of topological defects can be found in nanoscale non-uniform spin textures, such as monopoles, domain walls, vortices, and skyrmions.Recently, skyrmions stabilized by the Dzyaloshinskii-Moriya interaction have been studied extensively. However, the stabilization of antiskyrmions is less straightforward. Here, using numerical simulations we de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 63 publications
2
80
0
Order By: Relevance
“…This is in contrast to the isotropic behavior of skyrmions (the principal values are given by B xx = −B yy for antiskyrmions with γ = 0 in Figure 3, and B xx = B yy for Néel skyrmions) [56]. It is also possible to completely suppress the antiskyrmion Hall effect by properly choosing the direction of the charge current or by coupling skyrmions and antiskyrmions in a multilayer stack [56]. Note that antiferromagnetic skyrmions [61] or synthetic antiferromagnetic skyrmions in antiferromagnetically coupled layers [62,63] also exhibit a vanishing Hall angle.…”
Section: Dynamics Of Skyrmions and Antiskyrmionsmentioning
confidence: 81%
See 1 more Smart Citation
“…This is in contrast to the isotropic behavior of skyrmions (the principal values are given by B xx = −B yy for antiskyrmions with γ = 0 in Figure 3, and B xx = B yy for Néel skyrmions) [56]. It is also possible to completely suppress the antiskyrmion Hall effect by properly choosing the direction of the charge current or by coupling skyrmions and antiskyrmions in a multilayer stack [56]. Note that antiferromagnetic skyrmions [61] or synthetic antiferromagnetic skyrmions in antiferromagnetically coupled layers [62,63] also exhibit a vanishing Hall angle.…”
Section: Dynamics Of Skyrmions and Antiskyrmionsmentioning
confidence: 81%
“…Here, we discuss (anti)skyrmion dynamics due to STT and SOT induced by in-plane charge currents [56,31]. These two mechanisms differ as the former vanishes in the absence of magnetic textures while the latter does not.…”
Section: Dynamics Of Skyrmions and Antiskyrmionsmentioning
confidence: 99%
“…Moreover, the significant effects of the uniaxial stress on the stabilization of the skyrmion lattice have been revealed in earlier works [12][13][14][15]. On the skyrmion dynamics, it has been suggested that the skyrmions in chiral magnets can be effectively modulated by spin-polarized current [16][17][18][19], microwave fields [20], magnetic field gradients [21,22], electric field gradients [23][24][25][26], temperature gradients [27] etc. So far, some of these manipulations have been realized in experiments [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…They have been observed in chiral bulk helimagnets in the presence of bulk DMI [12][13][14][15] and in ultrathin magnetic films contacted with a heavy metal layer in the presence of interfacial DMI [16][17][18][19], respectively. Antiskyrmions with rotation symmetry breaking have been predicted in magnetic materials belonging to crystallographic classes D 2d and S 4 by Bogdanov et al [12], which have been investigated theoretically and experimentally in recent years [16,[20][21][22][23][24]. While for skyrmions or antiskyrmions, the angle of progressive magnetization rotation is 1π, where the angle is defined as the number of sign changes of the perpendicular magnetization when moving along the radial direction.…”
Section: Introductionmentioning
confidence: 99%